Removal of chromium with CNT coated activated carbon for waste water treatment - Kabbashi, Nassereldeen A.; Nour, Abdurahman Hamid; Al-Khatib, Ma'an Fahmi Rashid; Maleque, Md Abdul (Elsevier, 2020)
In this study, removal of chromium was accomplished by using carbon nanotubes from aqueous solution, with the optimization of process variables including the dose of initial pH, agitation speed, adsorbent, initial chromium concentration and contact time. The run orders for complete randomized experiment have been determined by using MINITAB fractional factorial design software. Fractional factorial designs are useful in factor screening because they reduced the number of runs to a manageable size. The runs performed are a selected subset or fraction of the full factorial design. The optimum conditions were determined to be pH 2.0, 100 ppm agitation speed, initial Cr(VI) concentration and application time of 60 min for 72% Cr (VI) removal. Adsorption kinetics study showed that the removal followed Langmuir equation model, it has been noted that activated carbon coated with carbon nanotubes (Type I) has the highest adsorption capacity of 11.57 mg/g followed by activated carbon coated with carbon nanotubes (Type II) and normal activated carbon. It has been calculated that activated carbon coated with carbon nanotubes adsorb 23.7% more compared to normal activated carbon. Same goes to Freundlich model where activated carbon coated with carbon nanotubes (Type II) has the highest adsorption capacity of 8.47 mg/g followed by activated carbon coated with carbon nanotubes (Type I) and normal activated carbon. It is also showed that activated carbon coated with carbon nanotubes has an adsorption capacity of 28.7% more than the normal activated carbon.